1984
DOI: 10.1111/j.1151-2916.1984.tb19644.x
|View full text |Cite
|
Sign up to set email alerts
|

CO2‐Catalyzed Surface Area and Porosity Changes in High‐Surface‐Area CaO Aggregates

Abstract: The changes in surface area and mesoporosity in aggregates of ∼0.01 μm cross‐section CaO particles when heated in CO2at 686°C were determined from N2 adsorption isotherms. Initially, the surface area decreases rapidly with little change in porosity. When the surface area has decreased below ∼90 m2/g, surface area and porosity variations become consistent with expectations for coarsening by grain‐boundary or bulk diffusion. The initial rapid decrease in surface area must result from CO2‐catalyzed surface diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 9 publications
4
42
1
Order By: Relevance
“…In the same table the data concerning the reagent grade of thermal decomposition of Calcite powders are reported. In agreement with the catalytic effect of the escaping CO2 on the sintering process of the CaO grains [5,7], it can be observed that the surface area of the CaO obtained from the decomposition of CaCO3 powders is always greater than the ones obtained from the decomposition of limestone pebbles, see Tab. 1.…”
Section: Background To the Wetting Heat Of Immersionsupporting
confidence: 74%
See 2 more Smart Citations
“…In the same table the data concerning the reagent grade of thermal decomposition of Calcite powders are reported. In agreement with the catalytic effect of the escaping CO2 on the sintering process of the CaO grains [5,7], it can be observed that the surface area of the CaO obtained from the decomposition of CaCO3 powders is always greater than the ones obtained from the decomposition of limestone pebbles, see Tab. 1.…”
Section: Background To the Wetting Heat Of Immersionsupporting
confidence: 74%
“…These morphological changes, cannot be due only to the effects of the LMST1 decomposition temperature. Indeed, when lime grains evolve from a round and/or polyhedrical shape to a flat one, others high temperature processes must occur [1], beside the ones due to the gas-solid reaction associated with the escaping CO2 [7,35]. Fig.…”
Section: Figure 4 Typical Sem Images At the Magnification Of 3000× mentioning
confidence: 99%
See 1 more Smart Citation
“…Hyatt, Cutler, andWadsworth (1958) previously observed that the diffusion of CO2 through CaCO3 layers during re-carbonation might occur. Beruto, Barco, and Searcy (1984) supported that the diffusion of CO2 through the carbonate product layer on the surface of micropores was restricted by grain boundary layer diffusion. Additionally, it has been suggested that theCO2 capture performance of Ca-based sorbents is enhanced by improving the diffusion of CO2 through the product layer (Yi et al 2009).…”
Section: Micro-scalementioning
confidence: 73%
“…The alternating progress of the capture and calcination processes also triggers a reduction in the active surfaces of the particles. This reduction is due to declining microporosity, which is caused by a more dense packing of CaO (cubic structure) compared with the packing of CaCO 3 (rhombohedral structure) 12 . CO 2 capture by activated CaO proceeds in two stages: the preliminary stage, characterised by a very high reaction rate; and the second stage, which is slow and is a consequence of CO 2 diffusion through the CaCO 3 layer.…”
mentioning
confidence: 99%